2021
DOI: 10.1371/journal.pntd.0009725
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-TOF mass spectrometry for the identification of freshwater snails from Senegal, including intermediate hosts of schistosomes

Abstract: Freshwater snails of the genera Biomphalaria, Bulinus, and Oncomelania are intermediate hosts of schistosomes that cause human schistosomiasis, one of the most significant infectious neglected diseases in the world. Identification of freshwater snails is usually based on morphology and, potentially, DNA-based methods, but these have many drawbacks that hamper their use. MALDI-TOF MS has revolutionised clinical microbiology and has emerged in the medical entomology field. This study aims to evaluate MALDI-TOF M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 86 publications
0
24
0
Order By: Relevance
“…Hamlili et al [29], have demonstrated that MALDI-TOF is a reliable tool for the rapid identification of frozen and ethanol-stored freshwater snails, permitting to distinguish intermediate hosts and non-intermediate hosts without any malacological expertise. In the present study, we confirm the usefulness of MALDI-TOF for malacological surveys in Schistosoma -endemic areas, enabling the rapid and reliable identification of emitted cercariae at species level and detection of hybrids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hamlili et al [29], have demonstrated that MALDI-TOF is a reliable tool for the rapid identification of frozen and ethanol-stored freshwater snails, permitting to distinguish intermediate hosts and non-intermediate hosts without any malacological expertise. In the present study, we confirm the usefulness of MALDI-TOF for malacological surveys in Schistosoma -endemic areas, enabling the rapid and reliable identification of emitted cercariae at species level and detection of hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…One of the limitations of MALDI-TOF is its inability to detect cercariae directly from snail’s tissues, making it impossible to identify pre- or non-patent infection [29]. However, the majority of pre-patent snails never realised their cercariae [53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MALDI-TOF MS has increasingly been used in the clinical microbiology field for rapid and reliable microorganism classification, and its advantages are currently driving its application in routine microbiological laboratories [ 26 ]. More recently, this proteomic tool has also proven its effectiveness in malacology [ 40 ]. Several entomological researchers have reported the usefulness of MALDI-TOF MS as a time-saving, effective and less laborious approach for the identification of various arthropods (ticks, fleas, mosquitoes, bed bugs, biting midges, triatomines), targeting different body parts used for protein extraction that generate specific spectra for each species [ 25 , 41 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The feet of the snails were used for MALDI-TOF MS identification as described by Hamlili et al . (2021) [21]. Each specimens’ MALDI-TOF MS spectra were then compared to the in-house snails reference spectra database (available at https://doi.org/10.35088/f605-3922)[21] using the MALDI-Biotyper v3.0 software (Bruker Daltonics).…”
Section: Methodsmentioning
confidence: 99%